2008
DOI: 10.1063/1.2927311
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional fifth-order Raman spectroscopy of liquid formamide: Experiment and Theory

Abstract: The fifth-order two-dimensional (2D) Raman spectrum of liquid formamide has been obtained. The absolute signal levels, qualitative features, as well as quantitative aspects of the 2D spectrum are found to be in good agreement with recent molecular dynamics calculations. The most important singular feature is the relatively strong rephasing signal observed along the diagonal. This finding illustrates the more structured nature of the hydrogen bond network of liquid formamide in comparison with simple liquids as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 99 publications
(204 reference statements)
1
71
0
1
Order By: Relevance
“…Such signals scale as N 2 and are known as cascading. The cascading signals have the same power dependence in the incoming fields and the same phase matching and are thus hard to distinguish from the direct signal [3][4][5][6][7][8][9]. In neat liquids, cascading dominates the direct signal due to the quadratic vs. linear scaling in molecular density.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such signals scale as N 2 and are known as cascading. The cascading signals have the same power dependence in the incoming fields and the same phase matching and are thus hard to distinguish from the direct signal [3][4][5][6][7][8][9]. In neat liquids, cascading dominates the direct signal due to the quadratic vs. linear scaling in molecular density.…”
Section: Introductionmentioning
confidence: 99%
“…An important example is the direct 5th-order Raman χ (5) process which is accompanied by a product of two 3rd-order χ (3) signals. Separating the two had drawn considerable attention and took several years to recognize [3,4,6,7,[10][11][12][13][14][15]. This has been the main obstacle for multidimensional Raman spectroscopy (5th-and-higher orders) [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…131 The homodyne-detected fifth-order Raman signal of formamide for the R (5) zzzz tensor element is shown in Figure 5. 131 The experimental results shown in Figure 5 have three distinctive features: (i) an absence of signal along t 2 , the time delay between the two "pump" pulses (four Raman pulses).…”
Section: D Raman Spectroscopymentioning
confidence: 99%
“…131 The homodyne-detected fifth-order Raman signal of formamide for the R (5) zzzz tensor element is shown in Figure 5. 131 The experimental results shown in Figure 5 have three distinctive features: (i) an absence of signal along t 2 , the time delay between the two "pump" pulses (four Raman pulses). Previously, it had been shown that four-wave mixing signals along t 2 may dominate the overall response of the 2D Raman experiment on carbon disulfide thereby masking the information content of the fifth-order data.…”
Section: D Raman Spectroscopymentioning
confidence: 99%